2009
DOI: 10.1002/acp.1554
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the modality and contiguity effects: New insights from investigating students' viewing behaviour

Abstract: The study examined viewing behaviour and learning outcome during multimedia learning in order to explore split-attention processes in modality and spatial contiguity effects. Fourty students viewed a computer instruction depicting the process of lightning. Exploratory text was spoken, written near or written far from accompanying animations. Students who received spoken text outperformed students who received written text in recalling the major steps (retention) and in identifying correct solutions to problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 22 publications
(38 reference statements)
1
32
2
6
Order By: Relevance
“…Thus, with sequential presentation the written text group was able to process the pictorial information adequately, resulting in no modality effect for pictorial recall with sequential presentation. This explanation receives further support from eye tracking studies showing that in multimedia learning environments learners predominantly read the text, whereas picture processing is secondary (e.g., Schmidt-Weigand et al, 2010). Thus, in system-paced learning environments, where the speed of presentation is typically determined by the time it takes to present the spoken text, it might be that for written text presentations the next slide is presented before the learner has had the chance to adequately process the picture, thereby yielding an insufficient processing of the pictorial information.…”
Section: 2mentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, with sequential presentation the written text group was able to process the pictorial information adequately, resulting in no modality effect for pictorial recall with sequential presentation. This explanation receives further support from eye tracking studies showing that in multimedia learning environments learners predominantly read the text, whereas picture processing is secondary (e.g., Schmidt-Weigand et al, 2010). Thus, in system-paced learning environments, where the speed of presentation is typically determined by the time it takes to present the spoken text, it might be that for written text presentations the next slide is presented before the learner has had the chance to adequately process the picture, thereby yielding an insufficient processing of the pictorial information.…”
Section: 2mentioning
confidence: 82%
“…Moreover, we added a picture-based retention test to complement the verbal, text-based recall measure (cf. Schmidt-Weigand, Kohnert, & Glowalla, 2010).…”
Section: The Present Studymentioning
confidence: 98%
“…Most importantly, the authors found no interference between written text and the spatial tapping task, which is not in line with the assumption that written text is initially processed in the visual/pictorial channel as proposed by the Cognitive Theory of Multimedia Learning and Cognitive Load Theory. For alternative explanations of the modality effect that are based on sensory memory rather than working memory processes, the reader is referred to Rummer et al (2010) and Schmidt-Weigand et al (2010.…”
Section: Verbal Informationmentioning
confidence: 99%
“…Learning with text and pictures thus appeared to be largely guided by the text in that the text base directs attention toward those parts of the picture that are addressed in the text. This idea of text-guided processing of pictures is well acknowledged in the literature on learning from text and pictures (e.g., Folker, Ritter, & Sichelschmidt, 2005;Hegarty & Just, 1993;Ozcelik, Arslan-Ari, & Cagiltay, 2010;Rummer, Schweppe, Fürstenberg, Scheiter, & Zindler, 2011;Schmidt-Weigand, Kohnert, & Glowalla, 2010a, 2010bSchwonke, Berthold, & zRenkl, 2009;Van Gog, Kester, Nievelstein, Giesbers, & Paas, 2009). …”
Section: Processing Of Text and Pictures In Multimedia Learningmentioning
confidence: 99%